Penerapan Teknologi Pembangkit Listrik Tenaga Surya Di Kampung Konservasi Glintung RW 23 Kelurahan Purwantoro Kecamatan Blimbing Kota Malang untuk Ketahanan Energi dan Konservasi Lingkungan (Fakultas Teknik, Universitas Brawijaya, 2025)
Solar Power Plants (PLTS) have several advantages, including being environmentally friendly because they do not produce greenhouse gas emissions, saving operational costs in the long term, and being an abundant and renewable energy source. PLTS is very suitable for areas that get a lot of sunlight, such as tropical countries including Indonesia. The implementation of alternatives to reduce dependence on fossil energy is carried out with the activity theme